Дослідження методів захисту інформації в банківських установах - Брайко, В. С.; Мартинчук, О. О. (ХНУРЕ, 2025)
The study examines comprehensive approaches to information security in banking institutions. The proposed model integrates physical, technical, and administrative protection methods, providing a multi-level security system adaptable to emerging threats. The research analyzes the economic efficiency of implementing advanced security solutions, including Next-Generation Firewalls, SIEM systems, and behavior analytics tools. The developed implementation plan enables banking institutions to systematically enhance their security posture while meeting regulatory requirements. Results demonstrate the importance of proactive security measures and continuous monitoring to reduce cyber incidents and financial losses in the banking sector.
Keywords: банк; захист інформації в банку